Correlation Between Anxiety, Diabetes-Related Distress, and Depression with Blood Glucose Outcomes of DM Type 2 Patients at Bhayangkara Sukanto Hospital in 2024 - Soeroso, Ratih Meireva; Febrian, Siti Nurwulan (Biomedika, 2025)
Diabetes mellitus is a chronic disease that can cause psychological distress such as anxiety, diabetes-related distress, and depression. This research is a retrospective non-experimental descriptive study that aims to analyze correlation between psychological distress and blood glucose outcome in type 2 Diabetes Mellitus patients at the internal medicine Bhayangkara Hospital in 2024. Of the 128 patients who met the criteria, the most patients were aged under 60 years (64.1%), the majority were female (61.7%), and the common drug use was oral medication (68%). The level of anxiety based on the GAD 7 scale was at a minimum level (47.7%). The highest level of difficulty for patients based on Diabetes Distress Screening Scale (DDS17) was at a high level of difficulty (50.8%). And the highest level of depression based on a PHQ 9 score was at the minimum level (43.8%). The results of the study, that there was a significant relationship between diabetes medication with blood glucose outcome in type 2 Diabetes Mellitus patients (P-Value <0.05). It can be concluded that there is no significant relationship between psychological distress and blood glucose outcome in type 2 Diabetes Mellitus patients at the internal medicine Bhayangkara Hospital in 2024.